(untitled) (Journal of Informatics and Mathematical Sciences, 2010)
In the last half century, topology as a subject has undergone vast changes. From its status of ``Rubber sheet geometry’’, topology has come a long way to be one of the most important subjects not only in Mathematics, but amongst various diverse systems and branches of modern sciences such as fuzzy logic, computing, artificial intelligence, pattern recognition, image–processing etc. In the process, the subject matter of topology has increased manifold. In this article, we discuss some of such new frontiers touched by topology. While interactions of logic programming and dislocated metric spaces are provided in detail, other areas are given only introductory mentions in the article.